QoS issues in ad hoc wireless networks. - Chakrabarti, S.
Ad hoc wireless networks consist of mobile nodes interconnected by multihop communication paths. Unlike conventional wireless networks, ad hoc networks have no fixed network infrastructure or administrative support. The topology of the network changes dynamically as mobile nodes join or depart the network or radio links between nodes become unusable. This article addresses some of the quality of service issues for ad hoc networks which have started to receive increasing attention in the literature. The focus is on QoS routing. This is a complex and difficult issue because of the dynamic nature of the network topology and generally imprecise network state information. We present the basic concepts and discuss some of the results. The article concludes with some observations on the open areas for further investigation
Keywords: QoS routing; Ad hoc wireless networks; Mobile nodes; Multihop communication paths; Network nodes; Network state information; Network topology; Quality of service; Radio links